Science Literacy through STEM-Based Project Based Learning Model - Hendrik Pratama; Matsun; Yulia Dewi Puspitasari; Tri Wahyuni Maduretno (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the project-based STEM (Science, Technology, Engineering and Maths) approach and its effect on science literacy. The research type is quasi-experiment with pretest postest nonequivalent control group design and 84 samples have been selected from 320 population. The project-based STEM approach was applied to the experimental class while the control class used the Problem Based Learning model. The results showed that the project-based STEM approach had a significant effect on science literacy. Measurement of science literacy in the experimental class showed better data than the control class where the assessment focused on aspects of content, process, context, and science attitudes. Students were able to connect science concepts with real-world scenarios. Another impact is that students are trained to work together in groups in developing ideas, solving problems using media projects, and drawing conclusions based on data analysis of investigation results. The novelty of this research is the creation of a new project in understanding nutrient material in the Basic Natural Science course. The resulting project is an IoT-based NPK, pH, temperature, conductivity, and humidity measuring instrument that can not only operate within the scope of the laboratory but can be disseminated to solve real problems.